The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2022
DOI: 10.3390/fermentation8030115
|View full text |Cite
|
Sign up to set email alerts
|

Bio-Based Processes for Material and Energy Production from Waste Streams under Acidic Conditions

Abstract: The revolutionary transformation from petrol-based production to bio-based production is becoming urgent in line with the rapid industrialization, depleting resources, and deterioration of the ecosystem. Bio-based production from waste-streams is offering a sustainable and environmentally friendly solution. It offers several advantages, such as a longer operation period, less competition for microorganisms, higher efficiency, and finally, lower process costs. In the current study, several bio-based products (o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 114 publications
0
4
0
Order By: Relevance
“…For instance, during the dark fermentation of 4% and 6% SCG medium-containing reactors, the pH dropped by 4.5 after the first day of fermentation, but interestingly, on the sixth and seventh days of fermentation, an increase in the pH to ~5.2 was observed, which consequently resulted in a hydrogen generation, especially in the 6% SCG-containing reactors, of ~1.2 dm 3 kg V.S −1 (Figure 4b). This fact once again underscores the importance of pH management for the optimal production and high yield of H 2 [39].…”
Section: The Effect Of Pretreatment On Biogas and Biohydrogen Productionmentioning
confidence: 78%
“…For instance, during the dark fermentation of 4% and 6% SCG medium-containing reactors, the pH dropped by 4.5 after the first day of fermentation, but interestingly, on the sixth and seventh days of fermentation, an increase in the pH to ~5.2 was observed, which consequently resulted in a hydrogen generation, especially in the 6% SCG-containing reactors, of ~1.2 dm 3 kg V.S −1 (Figure 4b). This fact once again underscores the importance of pH management for the optimal production and high yield of H 2 [39].…”
Section: The Effect Of Pretreatment On Biogas and Biohydrogen Productionmentioning
confidence: 78%
“…The pH value has tendency to evolve (i.e. acidify) during fermentation, but its control and stabilization as well as process microaeration showed increased H 2 yield (Cetecioglu et al 2022 ).…”
Section: Production Of Fuels Under Low Ph Conditionsmentioning
confidence: 99%
“…In order to make the process of biohydrogen production technically and economically feasible one needs to overcome several barriers and challenges which include: (i) the choice of inoculum and its pretreatment (stressing) in order to eliminate hydrogen consuming bacteria; (ii) the choice of substrate and suitable pretreatment methods (they vary for different substrates); (iii) lack of trace elements, especially iron and nickel, essential for hydrogenases (including (Fe), (NiFe)-, and (NiFeSe)-hydrogenase); (iv) high hydrogen partial pressure, which results in the reduction of oxidized ferredoxin, thus hindering hydrogen production; (v) scale-up methods—however, there are cases (still rare) of full-scale installation for biomethane, e.g. Ignaciuk and Ignaciuk (2018 ), Cetecioglu et al ( 2022 ); and (vi) low hydrogen yield (and inhibition caused by by-products, e.g. acetate, butyrate, and propionate).…”
Section: Production Of Fuels Under Low Ph Conditionsmentioning
confidence: 99%
See 1 more Smart Citation
“…There is a need for development of alternative methods of organic waste transformation into commercially profitable products, such as lipids, biomass, organic acids, biomethane, biohydrogen and others [3,4]. Recently, it was indicated that the little-known waste EAF is an excellent substrate with which to produce isocitric acid using the yeast Yarrowia lipolytica [5].…”
Section: Introductionmentioning
confidence: 99%